Perceived burdensomeness is associated with low‐lethality suicide attempts, dysfunctional interpersonal style, and younger rather than older age. (14th June 2016) - Vanyukov, Polina M.; Szanto, Katalin; Hallquist, Michael; Moitra, Modhurima; Dombrovski, Alexandre Y.
Abstract : Objectives: Perceived burdensomeness is thought to contribute to suicide risk. However, suicidal behavior is clinically and psychologically heterogeneous. Does a high level of perceived burdensomeness differentiate medically serious suicidal acts, most closely resembling death by suicide, from less serious ones? How is perceived burdensomeness related to dysfunctional personality dimensions implicated in suicide? We sought to answer these questions in a cross‐sectional, case–control study of adults, aged 42 years or older ( n  = 165). Methods: Participants were suicidal depressed with history of high‐lethality and low‐lethality attempts, depressed with serious suicidal ideation, depressed non‐suicidal, and psychiatrically healthy controls. Following detailed clinical characterization, we assessed perceived burdensomeness, the Big Five, impulsivity, and anger rumination. Results: Low‐lethality attempters reported the highest levels of perceived burdensomeness, followed by ideators, high‐lethality attempters, non‐suicidal depressed, and healthy controls. Group differences were robust to confounders, including demographics, severity of depression, and physical illness burden. In suicide attempters, perceived burdensomeness scaled positively with neuroticism, impulsivity, and anger and negatively with extraversion, conscientiousness, and age. Conclusions: Our findings suggest that perceived burdensomeness is most prominent in a subgroup of younger individuals with lower‐lethality suicide attempts and a dysfunctional interpersonal style. Older adults with high‐lethality attempts are surprisingly more resilient to the feelings of burdensomeness. Copyright © 2016 John Wiley & Sons, Ltd.